2023
DOI: 10.1111/apha.13926
|View full text |Cite
|
Sign up to set email alerts
|

The CaSR/TRPV4 coupling mediates pro‐inflammatory macrophage function

Abstract: Aim: Although calcium-sensing receptor (CaSR) and transient receptor potential vanilloid 4 (TRPV4) channels are functionally expressed on macrophages, it is unclear if they work coordinately to mediate macrophage function. The present study investigates whether CaSR couples to TRPV4 channels and mediates macrophage polarization via Ca 2+ signaling. Methods: The role of CaSR/TRPV4/Ca 2+ signaling was assessed in lipopolysaccharide (LPS)-treated peritoneal macrophages (PMs) from wild-type (WT) and TRPV4 knockout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…14 Another example of cellular plasticity is the "taskrelated" phenotypic switch macrophages typically undergo in the tissue, which is prompted by changes in their bio/mechanical environment and happens during different phases of acute and chronic inflammation. 15,16 And last, Clifford et al have recently come up with a novel model of Na+ uptake in the zebrafish gill, one of the model organs to study ion movements across epithelia which is characterized by "unparalleled plasticity". 17,18 In biomedicine, as stated above, plasticity no longer refers to plasticity of whole organisms only, but the cellular and even subcellular mechanisms which enable organisms to dynamically respond and successfully adjust.…”
Section: Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…14 Another example of cellular plasticity is the "taskrelated" phenotypic switch macrophages typically undergo in the tissue, which is prompted by changes in their bio/mechanical environment and happens during different phases of acute and chronic inflammation. 15,16 And last, Clifford et al have recently come up with a novel model of Na+ uptake in the zebrafish gill, one of the model organs to study ion movements across epithelia which is characterized by "unparalleled plasticity". 17,18 In biomedicine, as stated above, plasticity no longer refers to plasticity of whole organisms only, but the cellular and even subcellular mechanisms which enable organisms to dynamically respond and successfully adjust.…”
Section: Plasticitymentioning
confidence: 99%
“…Another example of cellular plasticity is the “task‐related” phenotypic switch macrophages typically undergo in the tissue, which is prompted by changes in their bio/mechanical environment and happens during different phases of acute and chronic inflammation 15,16 …”
mentioning
confidence: 99%
“…In this issue of the Journal, Chen and colleagues provide evidence for a functional coupling of the Ca 2+ ‐sensing receptor (CaSR) and the transient receptor potential vanilloid‐type 4 (TRPV4) cation channel that governs the plasticity of peritoneal macrophages (PMs) and promotes their differentiation into a pro‐inflammatory M1 phenotype 1 …”
Section: Figurementioning
confidence: 99%
“…In this issue of the Journal, Chen and colleagues provide evidence for a functional coupling of the Ca 2+ -sensing receptor (CaSR) and the transient receptor potential vanilloid-type 4 (TRPV4) cation channel that governs the plasticity of peritoneal macrophages (PMs) and promotes their differentiation into a pro-inflammatory M1 phenotype. 1 The cation channel TRPV4 is widely expressed in all tissues, including immune cells, and has a highly conserved role as mechanosensitive Ca 2+ channel. In macrophages, its function has been linked to the regulation of macrophage plasticity and their ability to switch phenotype.…”
mentioning
confidence: 99%
“…For example, Henry et al [16] showed that TRPV4 agonist increased Ca 2+ influx in human respiratory epithelial cells which further enhanced PGE2 production and IL-8 secretion [16]. Conversely, blocking the TRPV4 channel reduced Ca 2+ entry and lowered the level of the proinflammatory cytokine [17][18][19]. Similarly, H. Shannon et al [20] showed that mice receiving a daily intraperitoneal injection of GSK2193874 demonstrated reduced inflammatory cytokine IL-1β and inflammatory chemokine MIP2 [20].…”
Section: Introductionmentioning
confidence: 99%